Spontaneous synchronized tapping to an auditory rhythm in a chimpanzee - Hattori, Yuko (Nature Publishing Group, 2013)
Humans actively use behavioral synchrony such as dancing and singing when they intend to make affiliative relationships. Such advanced synchronous movement occurs even unconsciously when we hear rhythmically complex music. A foundation for this tendency may be an evolutionary adaptation for group living but evolutionary origins of human synchronous activity is unclear. Here we show the first evidence that a member of our closest living relatives, a chimpanzee, spontaneously synchronizes her movement with an auditory rhythm: After a training to tap illuminated keys on an electric keyboard, one chimpanzee spontaneously aligned her tapping with the sound when she heard an isochronous distractor sound. This result indicates that sensitivity to, and tendency toward synchronous movement with an auditory rhythm exist in chimpanzees, although humans may have expanded it to unique forms of auditory and visual communication during the course of human evolution.